Project-Based Learning Methodology as a Promoter of Learning Math Concepts: A Scoping Review - Cruz, Sara; Viseu, Floriano; Lencastre, José Alberto (Frontiers in Education, 2022)
The scoping review represents an important step towards constructing scientific knowledge on a topic in a sustained and integrated manner. Therefore, this article contemplates a scoping review of the resource on project-based learning in learning math concepts. This research resulted in 17 studies that were reviewed to establish connections between project-based learning and its potential to promote understanding of math concepts. All articles were collected in scientific journals subject to blind review available on open research online, identified as empirical studies. The research was organized around three central themes: math, project-based learning, and ICT technologies. Data analysis allowed the building of a model in which the empirical data on project-based learning in learning math concepts in terms of (i) the learning environment, (ii) the mathematic content, (iii) the process, and (iv) the student skills. The potential results suggest that project-based learning engages students in math learning environments. Project-based learning must be understood as a learning strategy to develop hard and soft skills related to mathematics. There is also evidence that project-based learning improves the integration of math concepts in a natural context, promotes differentiated teaching and enhances the student-centred logic in math education. Moreover, the retained partial results in the analysis showed the feasibility of this scoping review, thus providing a basis for developing a scoping review. The presented review can work as a guide for other scoping reviews and a model for reflecting on future action on the covered topics.